PROXIMATE AND AMINO ACID PROFILES OF SEED AND RIND OF THREE VARIETIES OF WATERMELON AND THEIR IMPLICATIONS FOR FISH NUTRITION - SOLOMON, S.G; JIMMY, U. J.; OBATANMI, S.W.; KWAGHVIHI, O.B.; DAUDA, A. B.; IKHWANUDDIN, M.; OKOMODA, V.T. (Nigerian Journal of Fisheries, 2023)
Unconventional feedstuffs are increasingly gaining relevance in on-farm diet prepared for animals in a bid to reduce cost of feeding. This study therefore aimed to analyze the proximate composition and amino acid profile of agricultural by-products specifically the rinds and seeds, derived from three different varieties of watermelon (Citrullus lanatus). The ripe samples of the three varieties of watermelon (namely, sugarbaby, greybelle and kaolack) collected from a local grocery point were washed and cut open, after which their pulp was removed. The rinds and seeds were then collected per variety, and the sundried, milled and subsamples were analysed for proximate and amino acid profiles. The findings revealed that the seeds exhibited higher levels of crude protein and fat contents (ranging from 17.75–18.45% for protein and 14.42–15.73% for fat) compared to the rind, where levels ranged from 8.44–12.16% for protein and 2.96–3.50% for fat. The greybelle and kaolack varieties of C. lanatus, exhibited the highest protein content in their seeds, surpassing that of conventional feed ingredient like maize. This indicates that these watermelon seeds are notably rich in protein content. Similarly, the essential amino acid profile also differed among the varieties’ by-products. The sugarbaby rind had the highest lysine content (5.25), while the lowest value (3.40) was found for the sugarbaby seeds. The methionine values of the kaolack seeds and sugarbaby rinds were greater (1.56 and 1.57, respectively) than those of their by-products. The levels of several of the essential amino acids recorded for the different varieties’ by-products were found to be greater than those previously reported for maize. It was concluded that the watermelon by-products of the different varieties may be considered nutritional alternatives to maize in the diets of fin and shellfishes.